2017
DOI: 10.2147/lra.s101373
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for the patient undergoing total knee replacement: current status and future prospects

Abstract: Total knee arthroplasty (TKA) has become one of the most common orthopedic surgical procedures performed nationally. As the population and surgical techniques for TKAs have evolved over time, so have the anesthesia and analgesia used for these procedures. General anesthesia has been the dominant form of anesthesia utilized for TKA in the past, but regional anesthetic techniques are on the rise. Multiple studies have shown the potential for regional anesthesia to improve patient outcomes, such as a decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 57 publications
2
53
0
Order By: Relevance
“…Therefore, they are highly sought after. Regional anesthesia is one candidate, demonstrating efficacious results with regard to pain and complication outcomes28; however, its use is associated with increased complexity, requirements for training, and potential complications. Widespread application of regional anesthetic techniques is not deemed feasible in all settings and is contraindicated in a number of settings, particularly when coagulation disorders are present 29.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are highly sought after. Regional anesthesia is one candidate, demonstrating efficacious results with regard to pain and complication outcomes28; however, its use is associated with increased complexity, requirements for training, and potential complications. Widespread application of regional anesthetic techniques is not deemed feasible in all settings and is contraindicated in a number of settings, particularly when coagulation disorders are present 29.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities exist in the type of intraoperative anesthesia and analgesia used during total joint replacement surgeries [58, 59]. Neuraxial anesthesia during major joint procedures has been associated with superior perioperative outcomes [6063]. However, a study of over 500,000 patients undergoing total knee arthroplasty or total hip arthroplasty from 2006–2010 showed that neuraxial anesthesia was used significantly less in Medicaid and Black patients [58].…”
Section: 0 Discussionmentioning
confidence: 99%
“…3 Therefore, they create new challenges in anesthesia protocols requiring dose optimization to allow immediate postoperative mobilization. 4,5 In fast-track TKA, intrathecal anesthesia is preferred over general anesthesia because of lower mortality and morbidity rates. [6][7][8][9] Moreover, spinal anesthesia yields lower postoperative pain scores and less nausea and vomiting after TKA.…”
Section: Résumémentioning
confidence: 99%